2020
DOI: 10.2478/jvetres-2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

Serum total antioxidant capacity and enzymatic defence of dogs with chronic heart failure and atrial fibrillation: a preliminary study

Abstract: IntroductionAtrial fibrillation may potentially contribute to oxidative stress to a greater extent than chronic heart failure. The aim of the study was to compare the serum total antioxidant capacity and enzymatic antioxidant defence of dogs with chronic heart failure and atrial fibrillation with those of subjects with chronic heart failure and sinus rhythm and healthy controls.Material and MethodsA total of 33 dogs were divided into three groups: dogs with chronic heart failure and atrial fibrillation (CHF + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…53 In the same way, the study by Michałek et al reported that serum CuZn-SOD activity and serum total antioxidant capacity were significantly lower in their study groups compared to in control animals; specifically, they found that catalase activity was significantly higher and plasma GPx activity was significantly lower in dogs with chronic heart failure and AF compared to those with chronic heart failure only, sinus rhythm, or control dogs. 54…”
Section: Superoxide Dismutase and Catalasementioning
confidence: 99%
“…53 In the same way, the study by Michałek et al reported that serum CuZn-SOD activity and serum total antioxidant capacity were significantly lower in their study groups compared to in control animals; specifically, they found that catalase activity was significantly higher and plasma GPx activity was significantly lower in dogs with chronic heart failure and AF compared to those with chronic heart failure only, sinus rhythm, or control dogs. 54…”
Section: Superoxide Dismutase and Catalasementioning
confidence: 99%
“…Members of the nonenzymatic antioxidants are, e.g.,: ascorbic acid, alpha-tocopherol, uric acid (UA) or glutathione (GSH). Oxidative stress biomarkers such as the activity of antioxidant enzymes and total antioxidant capacity or ROS concentration can correlate with the occurrence of arrhythmias (Türker et al, 2016;Yang et al, 2018;Adameova et al, 2020;Michałek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%